2018
DOI: 10.1021/acs.nanolett.8b00444
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Transport in 2D Heterostructures Mediated through h-BN Tunneling Contacts

Abstract: Understanding the electronic transport of monolayer transition metal dichalcogenides (TMDs) and their heterostructures is complicated by the difficulty in achieving electrical contacts that do not perturb the material. Typically, metal deposition on monolayer TMDs leads to hybridization between the TMD and the metal, which produces Schottky barriers at the metal/semiconductor interface. In this work, we apply the recently reported hexagonal boron nitride (h-BN) tunnel contact scheme to probe the junction chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 68 publications
2
44
0
Order By: Relevance
“…Atomic scale characterization of the interfaces by scanning transmission electron microscopy (STEM) has suggested that the degradation is associated with the damage of TMDs in the contact layer by invasion of metal atoms [12][13][14] . Interface engineering, such as insertion of additional vdW layers (graphene 15 , hexagonal boron nitride (hBN) 16 , etc. ), mechanical transfer of metal films 13 and incorporation with indium 17 , are explored to form ideal vdW contacts that are free from the chemical disorder.…”
mentioning
confidence: 99%
“…Atomic scale characterization of the interfaces by scanning transmission electron microscopy (STEM) has suggested that the degradation is associated with the damage of TMDs in the contact layer by invasion of metal atoms [12][13][14] . Interface engineering, such as insertion of additional vdW layers (graphene 15 , hexagonal boron nitride (hBN) 16 , etc. ), mechanical transfer of metal films 13 and incorporation with indium 17 , are explored to form ideal vdW contacts that are free from the chemical disorder.…”
mentioning
confidence: 99%
“…As shown in Figure S5a,b (Supporting Information), the I–V trends are asymmetric, which is likely due to the differences in energies between MoS 2 , WS 2 , and metal work functions at the contacts. This asymmetry in the transport curves about zero applied voltage is attributed to asymmetric Schottky barriers across the heterojunction . Briefly, due to differences in the energy levels of the sulfur vacancy states in MoS 2 compared to WS 2 , inequivalent Schottky barriers form at each metal/semiconductor interface leading to the observed current behavior.…”
mentioning
confidence: 99%
“…CVD assisted by sodium chloride (NaCl) requires lower growth temperatures, as Na precursors condensate on the substrate and reduce reaction energies [73]. Given that the properties of 2D materials are susceptible to external environments, the encapsulation of HSs between hBN sheets has been recently obtained [77], showing that both photovoltaic and hot electron generation lead to photocurrents that depend on the biasing conditions.…”
Section: Interfacementioning
confidence: 99%